An assessment of vaccine wastage in the Solomon Islands - Ibrahim Dadari; Laura Ropiti; Aven Patson; Philip Okia; Jenny Narasia; Timothy Hare'e; Salome Namohunu; Divinal Ogaoga; Jenny Gaiofa; Effua Usuf (Public Library of Science (PLoS), 2022)
Calculating vaccine wastage rates supports vaccine forecasting and prevents stock outs/over-stock at central and immunisation delivery facilities. Ensuring there are sufficient vaccines on the several small islands of The Solomon Island while minimising waste is a challenge. Twenty-two health facilities were selected randomly from six purposefully identified provinces in the Solomon Islands and across the different levels of the health service. Additional data were obtained from the national medical stores and the Expanded Programme on Immunisation (EPI) monthly reports for 2017 and 2018. All the selected facilities were visited to observe stock management practices. We calculated wastage rates for each vaccine antigen in the EPI and described the type of wastage. We found a wide variation in the average wastage rates at the second level medical stores which may be attributed to the partial availability of wastage data. The overall wastage rate for 20-dose BCG was 38.9% (18.5-59.3), 10-dose OPV was 33.6% (8.1-59.1), and single dose PCV was 4.5% (-4.4-13.5). The data from the two smaller and farthest provinces were incomplete/not available and did not contribute to the overall wastage rates. About 50% of the reported wasted doses at the facility were reported as "damaged" vials. Wastage rates were high for the multidose vials and slightly lower for the single dose vials which were also higher than the indicative rates. There is a need to improve recording of vaccine wastage through continuous monitoring for better forecasting and program effectiveness.